2021
DOI: 10.1016/j.mcpro.2021.100046
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Principles, Constraints, and Opportunities in Clinical Proteomics

Abstract: Recent advances in MS-based proteomics have vastly increased the quality and scope of biological information that can be derived from human samples. These advances have rendered current workflows increasingly applicable in biomedical and clinical contexts. As proteomics is poised to take an important role in the clinic, associated ethical responsibilities increase in tandem with impacts on the health, privacy, and well-being of individuals. We conducted and here report a systematic literature review of ethical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 78 publications
1
21
0
1
Order By: Relevance
“…At present, all PX resources are committed to completely open data, which means there are currently no limitations for data reuse by the community ( 19 ). One increasingly relevant topic is whether proteomics data from human samples can be used to identify individuals and whether proteomics data may be considered personally identifiable information ( 19 , 20 ). The privacy risks of proteomics data may emerge, and this issue will need to be properly assessed and managed.…”
Section: Discussion and Future Plansmentioning
confidence: 99%
“…At present, all PX resources are committed to completely open data, which means there are currently no limitations for data reuse by the community ( 19 ). One increasingly relevant topic is whether proteomics data from human samples can be used to identify individuals and whether proteomics data may be considered personally identifiable information ( 19 , 20 ). The privacy risks of proteomics data may emerge, and this issue will need to be properly assessed and managed.…”
Section: Discussion and Future Plansmentioning
confidence: 99%
“…Mann et al introduced the four core principles of bioethics: autonomy, justice, nonmaleficence, and beneficence. 191 From a systematic literature review of "ethics and clinical proteomics", they identified 10 normative themes: standards and QC, integration of new laboratory and computer technologies, privacy, discrimination, conflicting rights and duties, beneficence and justice, incidental findings, regulation, international guidance, and clarity of goals. They emphasize a dichotomy between actionable and nonactionable test results.…”
Section: ■ Ethical Considerationsmentioning
confidence: 99%
“…That said, we have noted an increasing tension between the imperatives for data accessibility, as formalized in the FAIR principles (Wilkinson et al, 2016), and the desire for data privacy, such as embodied in the GDPR regulation of the European Union (Ducato, 2020) (Figure 5). This has only recently become an issue in proteomics as data quality has increased to an extent that it potentially allows (re)identification of individuals, which now raises ethical and philosophical questions (Geyer et al, 2021;Mann et al, 2021). It is important that the different stakeholders and authorities recognize these challenges and deal with them in a way that does not prevent scientific and medical progress.…”
Section: Ai Supported Biomarker Discoverymentioning
confidence: 99%